2010
DOI: 10.1038/jcbfm.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Localized Blood—Brain Barrier Disruption using Focused Ultrasound can be Achieved at Short Pulse Lengths and Low Pulse Repetition Frequencies

Abstract: Ultrasound methods in conjunction with microbubbles have been used for brain drug delivery, treatment of stroke, and imaging of cerebral blood flow. Despite advances in these areas, questions remain regarding the range of ultrasound parameters that disrupt the blood-brain barrier (BBB). In this study, several conditions were investigated to either enhance or reduce the likelihood of BBB disruption. Pulsed focused ultrasound (frequency: 1.5 MHz, pressure: 0.46 MPa, pulse repetition frequency (PRF): 0.1 to 25 Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
120
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 27 publications
7
120
1
Order By: Relevance
“…Recent studies have shown that larger microbubbles (4-5 and 6-8 μm) have a lower PRP threshold for BBB disruption than smaller bubbles (1-2 μm) (9, 20) when using PLs greater than 66.7 μs. Also, previous work, which analyzed concentrations of 0.01 to 0.25 μL∕g, did not show any significant differences in drug delivery concentration (16), which was in good agreement with other studies that used similar parameters (15).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Recent studies have shown that larger microbubbles (4-5 and 6-8 μm) have a lower PRP threshold for BBB disruption than smaller bubbles (1-2 μm) (9, 20) when using PLs greater than 66.7 μs. Also, previous work, which analyzed concentrations of 0.01 to 0.25 μL∕g, did not show any significant differences in drug delivery concentration (16), which was in good agreement with other studies that used similar parameters (15).…”
Section: Discussionsupporting
confidence: 77%
“…In this paper, we demonstrated that BBB disruption may be achieved with as little as 5 pulses of 3.5 cycles (2.3 μs at 1.5 MHz) transmitted at a PRF of 100 kHz. Our previous work has demonstrated that 50 cycles (33 μs at 1.5 MHz) can induce BBB disruption (16). Increasing the number of emitted pulses, or the PL, increased the NOD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36,58 The observation of diffuse dye leakage along the length of the vessel was postulated to be due to transcellular passage compared to intense focal leakage, postulated to be due to paracellular transport. 36 Controlling the range of applied ultrasound pressure could be used to induce the different type of leakage following BBB disruption. Managing the leakage types, indicative of BBB disruption, may further improve drug delivery using FUS.…”
Section: ■ Cellular Mechanisms Of Fusmentioning
confidence: 99%